Learning disabilities: description, diagnosis or explanation? - Dale Baum; Maximo Plata (Educational Considerations, 1976)
This article explores the semantics of the term, "learning disabilities." As currently used, the term often tends to reflect the professional and/or personal interest of the user rather than a concern for the respect and treatment of the child so labeled. The authors suggest that if the field were re-oriented toward learning how to teach these children, it could, perhaps, evolve as an instructional discipline with more tangible benefits for the children, their teachers and their parents.